Transformasi Digital Bagi Siswa Tunarungu: Pelatihan SEO Copywriting Sebagai Peluang Karir - Kristanto, Barlian; Setia Sandi Ariyanto, Arif; Diannike Putri, Diannike Putri; Aulia Zilmi Kafah, Aulia Zilmi Kafah; Edgina Rangga Arkananta, Edgina Rangga Arkananta; Nur Arifin, Nur Arifin; Siti Shinta Yulistiyani, Siti Shinta Yulistiyani; Esa Aditya Kurniawan, Esa Aditya Kurniawan (Jurnal Arba - Multidisiplin Pengabdian Masyarakat, 2024)
Digital transformation provides opportunities for individuals from various backgrounds, including deaf students, to access careers in the digital world. This article discusses a community service program offering SEO copywriting training designed specifically for deaf students as an effort to enhance their skills in digital marketing. The training was conducted with an inclusive approach, adapting content and teaching methods to meet the communication needs of deaf students. Participants were introduced to the basics of SEO, effective content writing strategies, and search engine-friendly copywriting techniques. Evaluation results showed that participants experienced improved understanding and skills in SEO copywriting, as well as saw new career opportunities. This initiative also highlights the challenges deaf students face in learning and working in the digital field and provides recommendations for developing similar programs. This training program is expected to serve as a model that inspires digital empowerment efforts for people with disabilities as they navigate the era of digital transformation.